Música no Programa Mais Educação: um estudo sobre as práticas de canto coral em escolas paraibanas - Mendes, Josefa Eliane Ribeiro (2015)
The search for a quality public education in Brazil has mobilized the spheres of government at the federal, state and municipal levels and fueled many discussions about comprehensive education, leading them to invest in programs to expand the school day. The Programa Mais Educação (More Education Program) emerged from this perspective, with the objective of expanding time, space and educational opportunities. This program serves children and adolescents who study in public schools that have a low index of Basic Education Development (IDEB). The More Education Program offers numerous educational activities, including music, that is present in various workshops. This research investigates the process of teaching music through the More Education Program in two state schools from the state of Paraíba, with the goal of identifying and analyzing the educational practices and musical experiences developed in choral workshops. Using a qualitative approach, we chose a multi-case study conducted in two schools, one in the capital, João Pessoa, and the other in the town of Conde. Data were collected through systematic and consecutive observation of music teaching practices and semi-structured interviews with the agents involved and also the state program coordinator. Along with the field research, we conducted a bibliographic study on materials related to comprehensive education, full-time education, and choir practices, among other relevant themes, as well as official documents from the More Education Program, from the Web site of the Department of Education the State of Paraíba and also the Pedagogical Political Projects of the two schools involved in the research. Based on our observations of music teaching practices developed and also of the interviews conducted, we found that in school A the practice of this workshop had satisfactorily met the minimum requirements of the proposal of the More Education Program, and more than likely, this result may be related to the community involvement of the teacher who coordinated the activities of the program in this school. On the other hand, we found that the teaching of music in the choral singing workshop from school B had been conducted in a shallow manner, leaving the musical language in the background, emphasizing social aspects, but without establishing a relationship with the experience and background of the students. We concluded that, although the study of these two cases does not allow generalizations, the results found in these two distinct schools reflect the decentralization of the implementation of the program and the diversity of practices that enables distinct educational outcomes. We hope that this research can bring new ideas and new studies on the subject, aiming at the possibility of finding new and positive experiences that meet the purposes for music education in this context.